PELATIHAN KEWIRAUSAHAAN DAN PEMBUKUAN KEKINIAN DENGAN MENGGUNAKAN APLIKASI BUKU KAS - Terenggana, Candra Astra; Kusmawati, Kusmawati; Rinamurti , Micheline; Putri, Weny; Khairunnisa, Khairunnisa (Jurnal Abdimas Musi Charitas, 2021)
The aim of this community service activity is to provide assistance to partners, namely SMA Sjahkyakirti and other high school / vocational students in the city of Palembang as well as students with entrepreneurial Student Activity Units (UKM). The development of MSMEs in Indonesia provides opportunities for young people to be independent and develop their own businesses. However, this is not easy due to several factors such as the lack of knowledge about entrepreneurship and the difficulty of obtaining business capital. The assistance provided is in the form of training and providing insight into entrepreneurial motivation and knowledge related to making financial reports using the Cash Book application. Effective business records can create adequate financial reports and in the end are expected to gain the trust of debtors. The techniques used in this activity are virtual seminars, questions and answers, and discussions.